Social Media and Business Ethics in The Sharia Economy - Situmorang, Diana (Teunuleh Publisher, 2024)
The rapid digitalization has created an ethical vacuum in the Sharia economy, especially on social media platforms where the pursuit of profit often conflicts with Islamic values like ?idq (honesty) and amanah (trust). Current literature remains descriptive, lacking a robust Sociological or Applied Ethics framework to analyze this tension. This study performs a Systematic Literature Review (SLR) and an Integrative Thematic Analysis to examine the intersection between digital business practices and Islamic ethical standards. It specifically aims to construct a normative-analytical framework anchored in the concept of Maq??id al-Shar??ah (the objectives of Islamic law). The findings reveal that ethical deviations (e.g., halal-washing, consumer manipulation via algorithms) are common in the Digital Public Sphere. We propose that the Maq??id framework, particularly the safeguard of D?n (Religion) and M?l (Wealth), offers a critical lens to govern digital business conduct. This framework ensures that social media is utilized not merely for economic gain, but as an instrument of maslahah (public good) and Digital Da’wah. This study contributes significantly to the fields of Digital Ethics, Sociology of Religion, and Applied Islamic Economics by transforming abstract ethical principles into concrete, measurable standards for a sustainable and morally grounded Islamic digital economy.